Tourism and local identity generated by NHK's morning drama: The intersection of memory and imagination in Kobe. Issue 2 (1st August 2019) - Jang, Kyungjae
This article shows how the interplay of local memories, the imagined worlds of media products and tourism can redefine the image of a particular place. Using the concepts of 'places of memory' (Nora) and 'places of the imagination' (Reijnders), the author analyses how NHK's morning drama (asadora) Kazamidori (The Weather Vane) (1977–1978) had a significant impact on the development of Kobe's Kitanochō district. The fusion of local memory and the world imagined in the series has resulted in the foreign settlers' mansions (so-called Ijinkan) being developed into a tourism resource and declared a national cultural heritage. As the example of Kazamidori shows, certain aspects of local history are accentuated and others deliberately ignored in such processes of heritage building, while both the media and tourism can play an important role in placemaking.